Vocational School Students' Information and Communication Technology Self-Efficacy Beliefs and the Factors Affecting their Use of Such a Technology - Turel, Vehbi; Calik, Sinan; Doganer, Adem (Igi Global, 2015)
The purpose of vocational schools (VSs) in Turkey, which offer two-year degree courses, is to provide the students who have completed a high school programme successfully with practical introductory experience in skilled trades such as computing, electronics, mechanics, carpentry, construction, field crops, and so on. Those who complete a two-year VS degree successfully are also entitled to take the national exam to access the associate degrees so that they can study further two years and get a four year degree diploma instead of a two-year one. In this study, vocational school (VS) students' (i.e., age 17/18 and above) information and communication technology (ICT) self-efficacy beliefs and their level in use of certain common programmes at one of the colleges in the eastern part of Turkey were investigated in the spring of 2012. The study examined the VS students' (a) demographic background, (b) their ICT self-efficacy beliefs and (c) their ICT-using level in certain common programs. The VS students at four different departments (i.e., two-year degree courses) who were full-time were given the questionnaires to complete. 272 (N=272) participants completed them. The study was both quantitative and qualitative. The quantitative results were analysed with SPSS (i.e., descriptive statistics, ANOVA, Independent Samples Test). The qualitative data were analysed with examining the participants' responses gathered from the open-ended questions and focussing on the shared themes among the responses. The results revealed that the participants were ICT literate and users. They had positive ICT self-efficacy beliefs and their level in certain common programs was good. There were also statistical differences between their (a) ICT self-efficacy beliefs and (b) ICT level in certain common programs in terms of the length of ICT-use, the frequency of ICT-use, the place of ICT-access, and gender. The findings were consistent with the models and theories of technology engagement (i.e., theory of technology acceptance, the theory of reasoned action, the decomposed theory of planned behaviour, and the unified theory of acceptance and use of technology), which recognise facilitating or inhibiting conditions. The implications are (1) to provide (free) full-access to ICT in terms of technology availability and efficient resources, (2) to provide free efficient ICT courses and (3) to integrate ICT into teaching/learning.
Keywords: College Education; Facilitating or Inhibiting Conditions; ICT Self-Efficacy Beliefs; Information and Communication Technology (ICT); Turkey; Vocational School (VS) Students